PENGARUH METODE NUMBERED HEAD TOGETHER BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR DALAM MATERI BANGUN RUANG - Lilian Slow, Vera Riyanti, Merbela Triposa Nope, (Universitas Tanjungpura, 2020)
Appropriated learning method has an important role in achievement of a good learning outcomes. This study aims to find out the influence of Numbered Head Together learning method assisted by mathematical audio-visual media on learning outcomes in solid figure. This study used an experimental method in the form of One Group Pretest Posttest Design with the initial test and final test. The population of this study was the fifth grade students of Public Elementary School 01 Semanget consisting of 2 classes namely V-A and V-B. While the sampleof this research was the V-A class students. Data collection technique used test and documentation. The instrument of this study was the essay test. Based on the result of data analysis, the average of pretest was 46.65 and the posttest average was 70.55. The result of the paired samples t-test calculation in hypothesis testing are t count (8.410)>t table (2,024). It can be concluded that H a is accepted, it means that the Numbered Head Together method assisted byaudio visual mathematical media has a big influence on learning outcomes in solid figure. The calculation of the effect size using the Cohen formula obtaines of 1.82, this shows that the method of Numbered Head Together has a big influence on learning outcomes in the material of solid figure.